Replacement of concentrate mixture with different levels of water hyacinth (Eichhornia crassipes) in basal diet on feed intake and production performance of piglets - Tiwari, Megh Raj; Karki, Mukesh; Pandey, Luma Nidhi; Poudel, Nabaraj (Journal of Agriculture and Natural Resources, 2020)
An experiment was conducted on weaned piglets at Piggery Research Unit of Regional Agricultural Research Station (RARS), Tarahara, Sunsari from 12 September to 4 December 2019 for 84 days after adjustment period of seven days. Twenty piglets after weaning of 4-6 months age were allocated into four treatments each with 5 replications by using Completely Randomized Design. Four type of experimental diets were composed for experimental piglets. Piglets of T1 (control) group were provided adlib concentrate mixture, 95% concentrate feed + 5% water hyacinth (WH) were given to T2 group, 90% concentrate feed + 10 WH were offered to T3 group and piglets of T4 group were fed 85% concentrate feed + 15% WH as per their daily requirement. Feed and water hyacinth intake were recorded daily and body weight gain was measured once a week. Experiment revealed that feed and WH intake was highly significant (p<0.001) among treatment groups. Highest total body weight gain was obtained in control group (T1) (37.66 kg) followed by T3 (34.91 kg) and T2 (34.25 kg) which was non-significant among diet groups. Similarly, highest average daily gain was observed higher for T1 (control) group (448 g /day) followed by T3 and T2 group (415.59 and 407.73 g/day, respectively). Feed Conversion Ratio (FCR) was observed almost similar in all treatment groups (1:2 kg). Experiment suggested that concentrate mixture can be safely replaced with WH up to 15% without any adverse effect on body weight gain.